An ACO Algorithm for Sum-Rate Maximization Problem in Opportunistic Spectrum Allocation - Wei Fei; Yang Zhen (2008 4th International Conference on Wireless Communications, Networking and Mobile Computing, 2008)
A major problem of opportunistic spectrum allocation is how to maximize spectrum utilization given a bunch of available channels, i.e. sum-rate maximization problem, which is considered as a combinatorial optimization problem in our paper. ant colony optimization (ACO) is a well-known metaheuristic in which a colony of ants cooperate in exploring good solutions to a combinatorial optimization problem. In this paper, we present an MMAS algorithm for maximizing spectrum utilization based on ACO. Experimental results show improvements over existing algorithms for the sum-rate maximization problem in opportunistic spectrum allocation.